Analysis of the grain market problems in Ukraine based on logistics - Shandrivskа, O.; Romanus, I.; Shandrivskyi, V. (Видавництво Львівської політехніки, 2016)
There is made a comprehensive analysis of market conjuncture of grain in Ukraine, analyzed the problems of functioning and development of the grain industry on the work. There are highlighted factors of influence on the market conjuncture of grain during the formation of grain exports in comparison with the world leader. Before consideration are taken: the main pricing factor, the principle of pricing, cost structure availability of export duties, specificity of logistics, the structure of production and consumption e.g. There are systematized grain industry issues, their causes and way of resolving. Problems identified in the following areas: problems with the storage and transportation of grain by different modes of transport, information and technological support of transportation and warehousing cargo handling, quality control, entry barriers and functioning, inefficient logistics management agricultural companies etc. Problems are grouped by such the factors: problems as regards storing and transporting grain, quality control problems and another environmental problems. We have concluded regarding the perspective of development, the main of which are development of logistics infrastructure, improving the quality control system in accordance with international requirements and renovation of fixed assets of enterprises of agricultural complex. Комплексно проаналізовано кон’юнктуру ринку зернових в Україні, проблеми функціонування та розвитку зернової галузі. Висвітлено чинники впливу на кон’юнктуру ринку зернових під час формування експорту зерна порівняно з світовим лідером. До розгляду взято такі чинники: основний ціноутворювальний чинник, принцип формування ціни, рівень цін, наявність експортного мита, структура собівартості, специфіка виробництва та споживання, особливості логістики. Систематизовані проблеми зернової галузі, причини їх виникнення та способи розв’язання на засадах логістики. Проблеми ідентифіковано за такими напрямами: проблеми із зберіганням та транспортуванням зерна різними видами транспорту, інформаційне та технологічне забезпечення транспортно-складської вантажопереробки, контроль якості, бар’єри входу та функціонування, неефективне логістичне управління сільськогосподарськими компаніями тощо. Зроблено висновки щодо перспектив розвитку, основними з яких є розвиток логістичної інфраструктури, вдосконалення системи контролю якості відповідно до міжнародних вимог та оновлення основних фондів підприємств агропромислового комплексу.
Аналіз проблем розвитку ринку зерна в Україні на засадах логістики
Keywords: market conjuncture of grain; logistics of grain market; agricultural complex; problems of development of agricultural enterprises; кон’юнктура ринку зернових; логістика ринку зернових; агропромисловий комплекс; проблеми розвитку аграрних підприємств